Estudo imuno-histoquímico ampliado do músculo vasto lateral em paralisia periódica tirotóxica - Dorta, Haron Silva [UNIFESP] (2015)
Thyrotoxicosis is the most common cause of muscle paralysis in young males called thyrotoxic periodic paralysis (TPP), and is characterized by transient hypokalamia and hypophosphatemia under thyroid hormone excess. It remains unclear whether muscle biopsies can aid diagnosis and follow-up of TPP. We examined a muscle biopsy specimen of a long-term (over 8 years) TPP to seek for more specific muscle findings. Our patient presented with a heart rate of 98 bpm, diffuse goiter, and mild tremors in the hands when TPP was suspected. He was immediately started on propranolol to control adrenergic symptoms and to prevent new attacks of muscle weakness. Lab tests revealed elevated Ft4 >6.0 ng/dL, low TSH <0,05 mIU/L, and positive antibodies anti-thyroglobulin 164 IU/mL, therefore treated with methimazole. We observed type 2 fiber predominance in vastus lateralis muscle biopsy but no other histopathological TPP findings. No deleterious mutations were found in KCNJ18 but polymorphism grouped in different haplotypes. We concluded that apart from slow to fast-twitch fiber changes type-2 predominance, muscle pathology in TPP might remain unspecific even after long time of muscle complaints, thus refraining the use of this procedure on clinical practice for either diagnosis or follow-up.